A REVIEW OF MANAGING LOGISTICS SUSTAINABILITY FOR CRISIS PREPAREDNESS - Fazielah Mohamad (Tesis, 2018)
This project paper investigates the utilization of supply chain management procedures to overcome challenges experienced by logistics managers amid humanitarian aid activities.